Crescimento e composição químico-bromatológica da palma forrageira e do algodão sob irrigação suplementar - OLIVEIRA, José Fábio Ferreira de (2019)
Forage cactus and arboreal cotton are crops adapted to the semi-arid regions, providing livestock farmers with a safe source to feed their animals. Although it has good adaptability to regions with serious water restrictions, it is possible that both forage cactus and arboreal cotton reach higher values of biomass when subjected to water availability situations, even affecting their chemical-bromatological quality. The objective of this study was to evaluate the growth and chemical and bromatological composition of the forage cactus biomass of the cv. Orelha de Elefante Mexicana (Opuntia stricta Haw) and the aerial part of the arboreal cotton (Gossypium hirsutum L.r marie gallante Hotch) under supplementary irrigation. The experiments were carried out in the same time interval in nearby areas, at the school farm of the Federal Rural University of Pernambuco, Garanhuns Academic Unit, Garanhuns-PE. The cactus was established with spacing of 1.80 m by 0.40 m, with estimated density of 13.889 plants per hectare and cotton spacing of 1.20 m by 0.90 m, resulting in an estimated value of 9.259 plants per hectare. The experimental design was completely randomized with four replicates for both cultures. The irrigation was by drip irrigation as a volume of 41.6 m3ha-1 in the cactus and 62.5 m3 ha-1 in the cotton, in the frequencies of 0,0, 21, 14 and 7 days. Before harvesting, the growth of cotton and cactus was measured, and the yields of fresh and dry matter in addition to the biometric variables of the cladodes of the forage cactus were determined. The cotton was evaluated in dry and rainy season and the palm was in one and two cuts in 24 months. There was a reduction in the productivity of forage cactus with the increase of irrigation frequencies, independently of one or two cuts in 24 months. Regarding arboreal cotton, better answers were found for most variables, with increased water volume, either in the dry or rainy period. Supplementary irrigation had only influence on the crude protein concentration, degradability and in vitro digestibility of the dry matter of the forage cactus and presented a higher concentration of dry matter and ether extract in a cut at 24 months. While concentrations of total carbohydrates, neutral detergent fiber, acid detergent fiber and acid-digested lignin from arboreal cotton increased. Therefore, in the soil and climatic conditions of the Southern Agreste of Pernambuco, supplementary irrigation negatively and positively influences the growth and productivity of forage cactus and arboreal cotton, respectively.